X Chromosome Inactivation Pattern and Pregnancy Outcome of Female Carriers of Pathogenic Heterozygous X-Linked Deletions - Zhao, Yuanyin; Li, Jia; Dai, Limeng; Ma, Yongyi; Bai, Yun; Guo, Hong (Frontiers in Genetics, 2021)
Prenatal risk assessment of carriers of heterozygous X-linked deletion is a big challenge due to the phenotypic modification induced by X chromosome inactivation (XCI). Herein, we described four Chinese pedigrees with maternal-inherited X-deletions above 1Mb. The pathogenic evaluation revealed that all X-deletions are harmful to heterozygous carriers, however, the asymptomatic pregnant female carriers in these families tremendously complicate the prognostic assessment of the unborn heterozygous embryos. In this study, we detected the XCI pattern of eleven female carriers of heterozygous X-linked deletions and four non-carrier females in these families, especially performed the first prenatal XCI pattern analysis in a fetal female carrier of heterozygous PCDH19-deletion to make risk prediction. In an adult female who lost one copy of the terminal of X chromosome short arm (Xp), a region enriching a large number of XCI escapees, the expression level of representative XCI escape genes was also detected. Pregnancy outcomes of all families were followed up or retrospected. Our research provides clinical evidence that X-deletions above 1Mb are indeed associated with extremely skewed XCI. The favorable skewed XCI in combination with potential compensatory upregulation of XCI escapees would protect some but not all female carriers with pathogenic X-deletion from severe clinical consequences, mainly depending on the specific genetic contents involved in the deletion region. For PCDH19-disorder, the XCI pattern is considered as the decisive factor of phenotype expression of which, prenatal XCI assay using uncultured amniocytes could be a practicable way for risk prediction of this disease. These results provide valuable information about the usage of XCI assay in the prenatal risk assessment of heterozygous X-linked deletions.